Short communication The methods of treatment of an ingrown toenail - Kordiak, Jacek; Santorek-Strumiłło, Edyta J.; Brocki, Marian; Bartkowiak, Rafał; Jabłoński, Sławomir (Archives of Medical Science, 2005)
An ingrown toenail is an inflammatory process occurring as a result of ingrowing medial or lateral edge of the nail into the nail bed. There are various causes of this ailment. The most common are: wearing poorly fit footwear causing pressure on the nail bed from the outside, improper trimming of toenails, hereditary susceptibility, trauma, hidrosis, presence of a background systemic disease (e.g. obesity, diabetes), onychomycosis and some medicines (applied in psoriasis and protease inhibitors). The treatment depends on the progression of the ailment (preservative or surgical methods). The clinical analysis involved 156 patients suffering from an ingrown toenail and treated from the year 2000 until September 2005 in The Clinic of Thoracic Surgery, General Surgery and Oncology of Clinical University Hospital No. 2. The group included 115 males (74% of patients) and 41 females (26% of patients). The age of patients differed from 25 to 68 years (on average 43 years). We performed 174 operations of marginal resection of the nail and phenolisation of the matrix among 156 patients. 7 patients underwent the procedure on both sides and 4 patients in two toenails. The healing time of the postoperative wounds was 14-18 days. The recurrence of the ailment was found in 4 patients (2.5% of patients). There were no complications such as excessive bleeding or postoperative infection in the study group. The marginal resection of the nail connected with phenolisation of the matrix is a good method of treatment of an ingrown toenail as it causes few recurrences and complications.